Histomorphology of Thyroid Gland in Surti Goats (Capra hircus) - R. Menaka (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the thyroid glands of 30 Surti goats of three different postnatal age groups. The capsule of the thyroid gland was well distinguished by three layered as outer, middle and inner layer. The distinct layer differentiation was due to the amount of fat deposition which determined the thickness of the thyroid capsule. The connective tissue comprised of predominantly collagen fibers with few reticular fibers. . The trabeculae penetrated in to the glandular area and terminated with narrow tapering end in the centre of the thyroid gland. . The thyroid follicles were lined with simple low cuboidal and simple high cuboidal epithelium. The simple low cuboidal epithelium was observed while storing the colloidal substance in the thyroid follicles at resting stage. The simple high cuboidal epithelial lining was observed during the active stage of the thyroid follicles. The varying sizes of the follicles were observed the large and small follicles were dominantly seen throughout the glandular area. The parafollicular cells either arranged singly or in groups. The C cells were located in the interfollicular space with lightly stained cytoplasm and large spherical nucleus.